Enhanced production of bacterial hydrolytic endoglucanase enzyme using waste leaves of water hyacinth and its thermal stability under the influence of TiO2 nanoparticles - Khan M.; Singh T.; Pal D.B.; Khan S.; Ahmad S.; Jandrajupalli S.B.; Haque S.; Singh R.; Srivastava N. (My University, 2025)
Cellulases are the enzymes of broad industrial interests due to their versatile applications including biomass conversion processing. However, issues, e.g., high production cost of enzyme and lack of suitable bioprocess technology, are the main thirst of this area. Additionally, fungal strains are frequently reported for the cost-effective cellulase and its constituent enzyme production, whereas narrow data are present on bacterial cellulase production. In this study, enhanced endoglucanase (EG) production has been investigated using bacterial strain Bacillus subtilis PF_1. Herein, EG has been produced using waste leaves of water hyacinth (WH), employed as substrate following solid state fermentation (SSF). At an optimum concentration of WH substrate (5.0 g), Bacillus subtilis PF_1 could produce 17 IU/gds EG and 12 IU/gds FP activity in 30 h. Besides, the enzyme activity was further enhanced by changing the particles texture, and maximum 21 IU/gds EG activity was noticed at 30 h in case of rough surface (RS) of WH as compared to smooth surface (SS) which produced only 9 IU/gds. Further, the crude EG enzyme exhibited an optimum incubation temperature of 60 °C at pH 5.0 when it was treated with TiO2 nanoparticles (NPs). Moreover, the same enzyme has shown its half-life stability at 60 °C for 4.5 h in the presence TiO2 NPs and the optimum incubation pH 5.0. The present study may have potential applications for cellulase production using WH which is imperative for numerous industrial purposes such as paper/pulp industries, biopolishing, and biomass conversion processing. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.